Kontroversi Pembatalan Ayat Dalam Surah Al-Baqarah Menurut Ibnu Salamah - Ali Sati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
This paper discusses the controversy over the cancellation of verses in surah al-Baqarah according to Ibn Salamah, which in this paper focuses on disputes or differences of opinion in the cancellation of verses in surah al-Baqarah. To see this controversy, the writer analyzes it from Ibn Salamah's point of view through the literature relating to the topic of this paper. In this paper it is found that there are many differences of opinion in the cancellation of verses in Surah al-Baqarah.